MISKONSEPSI SISWA PADA MATERI OPERASI HITUNG BENTUK ALJABAR DI KELAS VII SMP KEMALA BHAYANGKARI - Purwanti, Putri; Halini, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study to know the form of misconceptions experienced by 7th Grade students of Kemala Bhayangkari Middle school in the material of Calculating Operations on Algebraic Forms. This study uses descriptive methods by case studies. The subjects used in this study were 5 7th Grade students of Kumala Bhayangkari Middle School. Determination of the subjects based on multiple choice test results which were then interviewed. The results show that students still had a lot of misconceptions when they multiplication and subtraction on algebraic forms. The misconceptions experienced by students in calculating operations on algebraic form  because students did not understand the concept of calculating algebraic operations. Students assume that the calculating operation of algebraic forms is  same as operation of integers. Students had less understood that algebraic forms can only be operated on similar terms. Less understanding of students caused by the lack of information obtained on a concept. The forms of misconception experienced by students are  misconception of generalization and misconception of notation. The form of generalization misconception experienced by students is that they assumed that an algebraic form has two different operations. While the misconception of notation experienced by students is that they ignore the operation symbols so  they are wrong in completing the answer.Keywords: Calculating Operation of Algebraic Form, Misconception